(3GdNWGH GdJQHhj hGdLfhSI aj cJH GdJQHjI GdhWfjI, GdMdbI GdChdi GdCSGSjI ef GdJYdje GdYGe aj dHfGfs - (3CjhH, ahRjs ((3HjQhJs (3JLeY GdHGMKGJ GddHfGfjGJs, 2004)
(3jaJQV GdeDda Cf GdcJGH GdeOQSj GddHfGfj GdLOjO dG HO Cf jNdh ef Cj fRYI SdHjI VO GdeQCI(B. (3hJJfGhd GdOQGSI eOi GdJRGe GdeDdajf GddHfGfjjf HGdJhLjgGJ GdQSejI YfO bjGege HJCdja cJH GdJQHjI GdhWfjI hGdJfTFI GdeOfjI, hGdi Cj MO JXgQ aj gPg GdcJH UhQI GdeQCI eSGhjI ddQLd(B. (3ceG JgOa GdOQGSI Edi GdNQhL HebJQMGJ JSGYO eDdaj GdcJH GdJYdjejI Ydi GdhUhd Edi cJGH eOQSj fGLM jajO aj JUhjH fXQI GdeYde hGdeJYde eYG Edi GdeQCI(B. (3GYJeOJ GdOQGSI GdefgL GdhUaj GdJMdjdj YHQ WQjbI JMdjd GdeMJhi HhLg YGe, hJbfjI JMdjd GdehVhYGJ HhLg NGU ajeG jJUd HehVhY GdeSGhGI Hjf GdLfSjf aj GdcJH(B. (3hbO bQCJ GdcJH eGOI GdHMK hMMOJ GdYfGUQ PGJ GdUdI HgPg GdeGOI hfSbJ hUfaJ aj YOO ef GdaFGJ(B. (3hJQGhMJ hMOI GdbjGS Hjf GdYfhGf hGdSWQ hGdabQI hGdLedI hGdOQS hGdUhQI(B. (3hNdUJ GdOQGSI Edi Cf ehbY GdeQCI aj GdcJH eMOhO HGdeYfi Gdcej ddcdeI NGUI aj GdfUhU HjfeG JfUa GdUhQ hGdQShe GdeQCI(B. (3hYdi eSJhi GdYdGbI Hjf GdLfSjf, JJahb YdGbGJ GdUHjGf HUhQI cGSMI aj GdcJH Ydi GdYdGbGJ GdJj JfSLgG GdHfGJ hjJSY EWGQgG GdYdGFbj Edi cGaI GdCTNGU aj GdHjJ hGdeOQSI hGdeLJeY(B. (3CeG Ydi UYjO GdegGe, aJZjH GdHfGJ Yf GdSGMI HUhQI THg JGeI aj GdfUhU ebGHd egGe cKjQI heJfhYI jbhe HgG GdUHjGf(B. (3hHGdfSHI ddYed hGdegf hGdhXGFa JcGO GdeQCI dG JXgQ aj GdfUhU, HjfeG jSHM GdQLd aj HMQ hGSY ef GdCYeGd hGdCTZGd, ceG Cf hVY GdeQCI aj GdUhQ ebHhd Edi MO cHjQ aj gPg GdaFI(B. (3ef LgI CNQi JZjH fTGWGJ GdeQCI JeGeG Yf GdfUhU hJUd Edi KdK fTGWGJ GdQLd aj GdUhQ(B. (3hJahb MUI GdQLd aj GdeHGOQGJ hGdbQGQGJ MUI GdeQCI, hdG jSJhj hVY GdeQCI hGdQLd aj cJH GdJQHjI EdG ef MjK SjWQI GdeXgQ GdNGQLj GdYUQj hGdHYO Yf GdRj GdJbdjOj(B.s
(3GdfhY (B: (3ebGds
Keywords: (3GdLfOQs; Gender; Public Sector Elementary Education Civic Education Textbooks; Secteur Public Cycle primaire Education Civique Livres Scolaires; Sexe; (3GdJYdje GdQSej GdeQMdI GdGHJOGFjI JYdje GdJQHjI GdhWfjI hGdJfTFI GdeOfjI GdcJGH GdeOQSjs